STRATEGI AKSELERASI PENINGKATAN PENDAPATAN PETANI JAMBU METE DI SULAWESI TENGGARA - WITJAKSONO, JULIAN; SULLE, AHMAD; RUKU, SUBAEDAH (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
The cashew nuts production in Southeast Sulawesi has been showed the indicated to decreasing productivity and production fluctuation for ten years between 1995 until 2004. The cashew farming in Southeast Sulawesi especially in Muna district such as center production showed the low income on household farmers. The review of this paper showed the actual condition with the cashew farmers in their villages in Muna district that there were many factors determinants, i.e. the availability capital, input production, cashew trees condition, land condition, technology, managerial, market institutions, farming instructors and financial institution. This paper has the objectives main to improving the cashew farmer’s condition needed to increase their income on household farmers. The strategy for improving the above condition i.e. integration farming system between animals and crops especially in their field of cashew trees, past harvesting, quality, and market and pattern crops for the land optimization after the rehabilitation cashew trees. The five above condition is the crucial determinants as the good strategy hope to improving their condition especially to increase the productivity and farmers income on household farming
Keywords: Cashew Nuts, Productivity, Farmers, Strategy, Improving, Condition